Fluoride modified liquid metal medium thermite and preparation method thereof

By combining fluoride, iron oxide with aluminum powder, liquid metal modified aluminum thermal agent is prepared, which solves the problems of limited energy density improvement of the existing aluminum thermal agent and aluminum powder adhesion, and improves the thermal performance and ignition combustion performance of aluminum powder.

CN119591461AActive Publication Date: 2025-03-11BEIJING INST OF TECH

Patent Information

Application Number
CN202411771177.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing aluminum thermal agent cannot be in close contact with aluminum at the microscope, resulting in limited energy density improvement, and fluorine-containing polymers can easily cause aluminum powder particles to stick together, affecting full combustion.

Method used

By combining fluoride, iron oxide with aluminum powder, liquid metal modified aluminum thermal agent is prepared, and Fe(PFO)3@LM-Al@Fe2O3 composite particles are formed by ultrasonic treatment and hydrothermal reaction, and efficient modification of aluminum powder is achieved.

Benefits of technology

The thermal performance and ignition combustion performance of aluminum powder are improved, and before the high-temperature thermal oxidation reaction temperature of aluminum powder is delayed to the melting point of 660℃, a breakthrough in the thermal mass transfer process of aluminum powder is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591461A_ABST
    Figure CN119591461A_ABST
Patent Text Reader

Abstract

The invention discloses a fluoride modified liquid metal medium thermite and a preparation method thereof, and belongs to the technical field of thermite preparation. Liquid metal is prepared by using Gallinstan eutectic; the method comprises the following steps: synthesizing aluminum powder and liquid metal by adopting a physical mixing and ultrasonic treatment method to obtain liquid metal modified aluminum; the preparation method comprises the following steps: adding FeCl3. 6H2O into a perfluorooctanoic acid aqueous solution, stirring and mixing, carrying out hydrothermal reaction, and washing the obtained product to obtain Fe (PFO) 3; the method comprises the following steps: mixing liquid metal modified aluminum with iron perfluorooctanoate, and carrying out ultrasonic treatment to obtain Fe (PFO) 3-coated LM-Al; fe (PFO) 3 (at) LM-Al and ferric oxide are added into absolute ethyl alcohol for ultrasonic stirring and mixing, and Fe (PFO) 3 (at) LM-Al (at) Fe2O3 is prepared. By the adoption of the method, the high-temperature thermal oxidation reaction temperature of the aluminum powder is increased to be before the melting point of 660 DEG C, and the breakthrough progress of the aluminum powder thermal mass transfer process is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermite preparation, in particular to a fluoride-modified liquid metal medium thermite and a preparation method thereof. Background Art

[0002] Aluminum powder is easily oxidized at room temperature, and the Al2O3 generated on the surface will hinder the heat and mass transfer of aluminum powder and affect the contact between the internal aluminum core and the external oxygen environment. Therefore, the aluminum powder needs to be modified. In the existing research, nano-metal oxides are generally added to the micro-nano aluminum powder system, and composite thermites are prepared by physical mixing methods to improve the thermal properties and ignition and combustion properties of aluminum powder. Although this method can improve the thermal properties of aluminum powder, the thermite obtained by this process has limited effect on promoting the heat release of aluminum powder. At the microscopic level, the nano-metal oxides and aluminum cannot be in close contact with each other, and the energy density of the system has a large room for improvement.

[0003] Fluorine-containing polymers have been proven to effectively promote the energy release of aluminum powder. However, polymers have a long-chain random coil structure at the microscopic level, which can easily cause aluminum powder particles to stick together, thereby preventing the aluminum particles from fully burning and releasing energy.

[0004] Selecting fluorine-containing small molecules to coat aluminum powder can avoid the problems caused by high molecular weight fluoride coating of aluminum powder. However, in existing studies, the thermal stability of small molecules is poor and the fluorine content is not high, which affects the stability of aluminum powder and has limited catalytic effect. Summary of the invention

[0005] The purpose of the present invention is to provide a fluoride-modified liquid metal medium thermite and a preparation method thereof to solve the above problems.

[0006] To achieve the above object, the present invention provides a fluoride-modified liquid metal medium thermite and a preparation method thereof, wherein a high-activity thermite is prepared by compounding fluoride, iron oxide and aluminum powder, and the preparation method specifically comprises the following steps:

[0007] Step 1, preparation of liquid metal: using Galinstan eutectic of Ga: In: Sn = 68: 22: 10, with a melting point of -19°C, to prepare liquid metal, the obtained liquid metal is convenient for mechanical stirring at room temperature;

[0008] Step 2, preparation of aluminum powder / liquid metal composite energetic particles: synthesizing aluminum powder and liquid metal by physical mixing and ultrasonic treatment to obtain liquid metal modified aluminum;

[0009] Step 3, preparation of iron perfluorooctanoate: adding FeCl3·6H2O to a perfluorooctanoic acid aqueous solution, stirring and mixing, and then performing a hydrothermal reaction. The obtained product is washed to obtain Fe(PFO)3;

[0010] Step 4, preparation of Fe(PFO)3@LM-Al perfluorooctanoate iron-liquid metal modified aluminum composite particles: mixing liquid metal modified aluminum with perfluorooctanoate iron, and preparing a thermite by ultrasonic treatment;

[0011] Step 5, preparation of Fe(PFO)3@LM-Al@Fe2O3 energetic compound: Fe(PFO)3@LM-Al and iron oxide were added into anhydrous ethanol in a mass ratio of 4:3 and ultrasonically stirred and mixed to obtain Fe(PFO)3@LM-Al@Fe2O3.

[0012] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and its preparation method, the specific process of step 2 is as follows: use ultrasonic stirring with a power of 200 W and a frequency of 40 kHz to mix the aluminum powder and the liquid metal for 8 hours, and then perform vacuum filtration to obtain liquid metal-modified aluminum.

[0013] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and preparation method thereof, the proportion of liquid metal is adjusted to 10% when the aluminum powder and liquid metal are mixed.

[0014] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and preparation method thereof, the obtained liquid metal-modified aluminum is dried in an oven at 50° C. for 12 hours.

[0015] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and preparation method thereof, the specific preparation process in step 3 is as follows: add 10 mL of 0.1 mmol·mL -1 Perfluorooctanoic acid aqueous solution: weigh 4 mmol FeCl3·6H2O and add it to the perfluorooctanoic acid aqueous solution; after fully stirring the mixed solution at 50°C for 1 hour, transfer it to a hydrothermal kettle and react it in an oven at 100°C for 12 hours to obtain a product after the reaction.

[0016] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and preparation method thereof, the obtained product is finally washed and dried in an oven at 60° C. for 24 hours to obtain perfluorooctanoate iron.

[0017] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and its preparation method, the specific preparation process in the step four is as follows: using ultrasonic stirring with a power of 200 W and a frequency of 40 kHz, the liquid metal-modified aluminum and Fe(PFO)3 are ultrasonically stirred in 20 ml of anhydrous ethanol until the solvent is completely evaporated; the obtained mixture is vacuum filtered and dried in an oven at 50°C for 12 hours to obtain Fe(PFO)3@LM-Al.

[0018] Preferably, in the above-mentioned fluoride-modified liquid metal medium thermite and its preparation method, the ultrasonic stirring conditions in step five are to stir the mixture under ultrasonic stirring with a power of 200 W and a frequency of 40 kHz, and the obtained mixture is dried in an oven at 50°C for 12 hours to obtain Fe(PFO)3@LM-Al@Fe2O3.

[0019] Therefore, the present invention adopts a fluoride-modified liquid metal medium thermite of the above structure and its preparation method, and uses liquid metal to initially embrittle the aluminum shell, so that the hard outer shell of the aluminum shell is weakened. The gaseous small molecules produced by the decomposition of fluoride react with the aluminum powder to undergo a pre-ignition reaction, destroying the embrittled aluminum shell. At the same time, this process releases heat, further promoting the rupture of the embrittled aluminum shell; after the above steps, cracks are generated in the aluminum shell, and the internal aluminum core is initially in contact with the external oxidation environment through the cracks, and an aluminothermic reaction occurs. The heat released by the aluminothermic reaction back-attacks the aluminum particles, playing a positive cycle role, further promoting the rupture of the aluminum shell, and more aluminum cores are melted and contacted with the external oxygen environment, thereby improving its thermal performance and ignition and combustion performance. The present invention innovatively introduces liquid metal to etch the surface of aluminum powder, and prepares high-purity fluoride Fe(PFO)3, which forms composite particles with LM-Al core-shell, and further coats iron oxide particles on its surface to form a composite energetic compound. The fluoride and aluminum powder are pre-ignited and exothermic to increase the high-temperature thermal oxidation reaction temperature of the aluminum powder to before the melting point of 660°C, thereby achieving a breakthrough in the heat and mass transfer process of the aluminum powder.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 FTIR spectra (a), XRD patterns (b), SEM images (c) and TG-DTG curves (d) of Fe(PFO)3 and PFOA perfluorooctanoic acid prepared in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention;

[0022] Figure 2 (a) SEM and (b) EDS images of Fe(PFO)3@LM-Al composite particles in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention;

[0023] Figure 3 (a) FTIR spectrum and (b) XRD diagram of Fe(PFO)3@LM-Al composite particles in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention;

[0024] Figure 4TG-DSC curve of Fe(PFO)3@LM-Al composite particles in N2 atmosphere in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention;

[0025] Figure 5 The SEM and EDS images of Fe(PFO)3@LM-Al@Fe2O3 composite particles in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to the present invention;

[0026] Figure 6 (a) XRD and (b) XPS graphs of Fe(PFO)3@LM-Al@Fe2O3 composite particles in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention;

[0027] Figure 7 This is the TG-DSC curve of Fe(PFO)3@LM-Al@Fe2O3 in a fluoride-modified liquid metal medium thermite and a preparation method thereof according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0030] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0031] The present application provides a fluoride-modified liquid metal medium thermite and a preparation method thereof. The high-activity thermite is prepared by compounding fluoride, iron oxide and aluminum powder. The preparation method specifically comprises the following steps:

[0032] Step 1, preparation of liquid metal: using Galinstan eutectic of Ga: In: Sn = 68: 22: 10, with a melting point of -19°C, to prepare liquid metal, the obtained liquid metal is convenient for mechanical stirring at room temperature;

[0033] Step 2, preparation of aluminum powder / liquid metal composite energetic particles: synthesize aluminum powder and liquid metal by physical mixing and ultrasonic treatment to obtain liquid metal modified aluminum; use ultrasonic stirring with a power of 200 W and a frequency of 40 kHz to mix the aluminum powder and liquid metal for 8 hours, and then vacuum filter to obtain liquid metal modified aluminum; when the aluminum powder and liquid metal are mixed, the proportion of liquid metal is adjusted to 10%; the obtained liquid metal modified aluminum is dried in an oven at 50°C for 12 hours.

[0034] Step 3, preparation of perfluorooctanoic acid iron: add FeCl3·6H2O to the perfluorooctanoic acid aqueous solution, stir and mix, and then perform a hydrothermal reaction. The obtained product is washed to obtain Fe(PFO)3; add 10mL of 0.1mmol·mL -1 Perfluorooctanoic acid aqueous solution, weigh 4 mmol FeCl3·6H2O and add it to the perfluorooctanoic acid aqueous solution; the mixed solution is fully stirred at 50°C for 1 hour and then transferred to a hydrothermal kettle, and reacted in an oven at 100°C for 12 hours to obtain a reaction product, and finally the obtained product is washed and dried in an oven at 60°C for 24 hours to obtain iron perfluorooctanoate.

[0035] Step 4, preparation of Fe(PFO)3@LM-Al perfluorooctanoate iron-liquid metal modified aluminum composite particles: liquid metal modified aluminum and perfluorooctanoate iron are mixed, and aluminothermic agent is prepared by ultrasonic treatment; liquid metal modified aluminum and Fe(PFO)3 are ultrasonically stirred in 20 ml of anhydrous ethanol with a power of 200 W and a frequency of 40 kHz until the solvent is completely evaporated; the resulting mixture is vacuum filtered and dried in an oven at 50°C for 12 hours to obtain Fe(PFO)3@LM-Al.

[0036] Step 5, preparation of Fe(PFO)3@LM-Al@Fe2O3 energetic compound: Fe(PFO)3@LM-Al and iron oxide were added into anhydrous ethanol in a mass ratio of 4:3, and the mixture was stirred under ultrasonic stirring at a power of 200 W and a frequency of 40 kHz, and the obtained mixture was dried in an oven at 50°C for 12 hours to obtain Fe(PFO)3@LM-Al@Fe2O3.

[0037] The product obtained by the above steps is subjected to morphological characterization and analysis, and the detection method is as follows:

[0038] The microstructures of Fe(PFO)3, Fe(PFO)3@LM-Al, and Fe(PFO)3@LM-Al@Fe2O3 were studied by scanning electron microscopy (SEM, ZEISS GeminiSEM 300, Germany). The test conditions were: acceleration voltage 10V, probe beam current 3pA-20nA.

[0039] The phase compositions of Fe(PFO)3, Fe(PFO)3@LM-Al, and Fe(PFO)3@LM-Al@Fe2O3 were obtained by X-ray diffractometer (XRD, Rigaku Ultima IV, Japan). The test conditions were: wavelength Voltage 40kV, current 40mA.

[0040] The chemical compositions of Fe(PFO)3 and Fe(PFO)3@LM-Al were tested by Fourier transform infrared spectrometer (Thermo Fisher Scientific Nicolet iS20, USA) under the following test conditions: resolution 4 cm -1 , the scanning times are 32 times, and the test wave number range is 400 / 600-4000cm -1 .

[0041] The elemental composition and relative content of Fe(PFO)3@LM-Al@Fe2O3 were studied by X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha, USA). The test conditions were: the excitation source was Al Kα ray (1486.6eV), and the beam spot was 400um.

[0042] The characterization and analysis process of Fe(PFO)3 is as follows: Figure 1 As shown in Figure 1 (a) FTIR spectrum, (b) XRD pattern, (c) SEM image and (d) TG-DTG curve of the prepared Fe(PFO)3 and PFOA perfluorooctanoic acid.

[0043] Figure 1 The FTIR spectrum of Fe(PFO)3 in (a) shows that PFOA -1 The free COOH band at 1686.96 cm-1 no longer has stretching vibrations. -1 and 1651.28cm -1 A new absorption peak appears at the 3+ The stretching vibration of Fe 3+ Successfully replaced the H + It also further confirmed that there was no residual PFOA in the product, and it reached a high purity. Figure 1 (d) The results of TG-DTG are consistent. At the same time, 1148.88cm -1 and 1208.18cm -1 The peaks at 984 cm are attributed to the symmetric stretching vibration (νs-Cf2) and antisymmetric stretching vibration (νas-CF2) of FCF. -1 and 1452cm -1 The infrared absorption peaks at 1600-500 cm-1 belong to the symmetric stretching vibration of the F-CF2 functional group (vas-(F-CF2-)) and the antisymmetric stretching vibration of the CF3-CF2 functional group (vCF3-CF2). -1 The results show that the reaction products retain the fluorinated alkyl groups, which hardly participate in the chemical reaction.

[0044] Figure 1 (b) shows the XRD curves of PFOA and Fe(PFO)3. The characteristic diffraction peak of PFOA disappears, and a new characteristic diffraction peak of Fe(PFO)3 is formed, indicating that Fe(PFO)3 is a crystalline organic salt. The intensity of the characteristic diffraction peak of Fe(PFO)3 is slightly lower, which is attributed to its low crystallinity.

[0045] Figure 1 The SEM image of Fe(PFO)3 in (c) shows that the prepared perfluorooctanoate iron presents a micron-like flake structure with a certain thickness. This structure is conducive to forming a coating film on the surface of spherical aluminum powder particles to obtain core-shell structure composite particles.

[0046] The TG-DTG curve of prepared Fe(PFO)3 is as follows Figure 1 As shown in (d). PFOA will sublime before 150°C, resulting in almost 100% weight loss, and the maximum mass loss peak appears at 139.02°C on its DTG curve. However, the prepared Fe(PFO)3 has no obvious mass loss in the low temperature stage, indicating that it has reached a high purity and there is almost no residual PFOA. The peak temperature of the main thermal weight loss stage of Fe(PFO)3 is 340.47°C, and the decomposition of perfluorooctanoic acid iron is basically complete in this stage. Compared with PFOA, the prepared Fe(PFO)3 has a high thermal stability, which is conducive to its application in energetic materials.

[0047] The characterization of Fe(PFO)3@LM-Al was analyzed, such as Figure 2-4 As shown, Figure 2 (a) SEM and (b) EDS images of Fe(PFO)3@LM-Al composite particles; Figure 3 (a) FTIR spectrum and (b) XRD pattern of Fe(PFO)3@LM-Al composite particles; Figure 4 TG-DSC curve of Fe(PFO)3@LM-Al composite particles under N2 atmosphere.

[0048] Depend on Figure 2 From the SEM and EDS images of the Fe(PFO)3@LM-Al composite particles, it can be seen that the content of perfluorooctanoate iron in the sample accounts for 20%, and obvious warping flakes appear on the surface of LM-Al, such as Figure 2 (a). From the F element spectrum of Fe(PFO)3@LM-Al, it can be seen that the fluorine element is evenly distributed on the surface of the aluminum powder, which also shows that Fe(PFO)3 has a good coating effect. In addition, compared with LM-Al, the surface layer of Fe(PFO)3@LM-Al also contains O and Fe elements, which also confirms the formation of a Fe(PFO)3 coating layer on the surface of LM-Al. Core-shell Fe(PFO)3@LM-Al composite particles were successfully prepared.

[0049] In order to further confirm the formation of the perfluorooctanoate iron coating layer on the surface of aluminum particles, the composite particles were tested by FTIR and XRD. The FTIR spectrum of Fe(PFO)3@LM-Al composite particles is shown in Figure 2. Figure 3 (a) As shown. Fe(PFO)3@LM-Al composite particles at 1147.92 cm -1 and 1204.81cm -1 The infrared absorption peaks at 1640.64 cm-1 can be attributed to the symmetric stretching vibration (vs-CF2) and antisymmetric stretching vibration (vas-CF2) of FCF. In addition, the O=CO group was also detected in the FT-IR spectrum of Fe(PFO)3@LM-Al composite particles. -1 and 1679.21cm -1 This indicates that the aluminum particles are successfully coated by the Fe(PFO)3 film.

[0050] observe Figure 3 (b) shows the XRD pattern of Fe(PFO)3@LM-Al composite particles, which shows the significant characteristic diffraction peak of aluminum. Further zooming in on the XRD pattern details of the composite particles, a characteristic diffraction peak of Fe(PFO)3 was found near 17.9°, indicating that Fe(PFO)3 was successfully attached to the surface of aluminum particles, but due to the relatively low degree of crystallization of perfluorooctanoic acid iron, the diffraction peak intensity of perfluorooctanoic acid iron appeared weak.

[0051] Figure 4(a) shows the mass change of Fe(PFO)3@LM-Al composite particles during the heating process. It can be seen that the modified aluminum powder has three weight change stages: thermal weight loss occurs around 340℃, which is attributed to the thermal decomposition of Fe(PFO)3; thermal weight gain occurs around 600℃, which is attributed to the thermal oxidation of the solid aluminum surface to form Al2O3; thermal weight gain occurs between 800℃ and 1100℃, which is attributed to the thermal oxidation process of molten aluminum. Figure 4 (b) It can be seen that the modified composite particles have an exothermic peak at around 375°C, which is attributed to the pre-ignition reaction between the coating layer Fe(PFO)3 and the aluminum particles; the endothermic peak at 646°C is the melting of the solid modified aluminum; the exothermic peak after 800°C is attributed to the thermal oxidation of the molten aluminum. These phenomena are consistent with Figure 4 (a) corresponds to the TG test results.

[0052] The characterization of Fe(PFO)3@LM-Al@Fe2O3 was analyzed, such as Figure 5-6 As shown, Figure 5 The SEM and EDS images of Fe(PFO)3@LM-Al@Fe2O3 composite particles; Figure 6 (a) XRD and (b) XPS patterns of Fe(PFO)3@LM-Al@Fe2O3 composite particles.

[0053] Figure 5 It can be seen that under the modification process adopted in the present invention, iron oxide is uniformly coated on the surface of Fe(PFO)3@LM-Al. Figure 6 As shown in (a), the XRD spectrum is mainly composed of aluminum peaks (2θ = 38.4°, 44.7°, 65.1°, 78.2° and 82.4°) and Fe2O3 peaks (2θ = 24.1°, 33.1°, 35.6°, 49.4° and 62.4°). The results show that the phase structure of Fe(PFO)3@LM-Al@Fe2O3 has not changed compared with aluminum powder.

[0054] The elemental composition of Fe(PFO)3@LM-Al@Fe2O3 composite particles was further characterized by X-ray photoelectron spectroscopy. Figure 6(b). Analysis shows that in the Fe(PFO)3@LM-Al@Fe2O3 sample, there are not only typical signals related to Al 2p, Al 2s, O1s and C 1s, but also significant signals related to Ga (23.21eV, 160.18eV, 1117.25eV and 1144.18eV), In (443.8eV) and Sn (485.77eV, 494.65eV). It can be seen that the surface of the aluminum powder particles is covered by liquid metal (Ga, In, Sn). It can also be seen that the binding energy belonging to Fe (55.20eV, 710.15eV, 723.66eV) appears in the figure. It can be inferred that in this process, LM-Al and the oxide are modified to form a tightly wrapped core-shell structure.

[0055] The thermal performance characterization analysis and detection of the product prepared in this application are carried out as follows:

[0056] The thermal properties of the samples were investigated by thermogravimetric-differential scanning calorimetry (TG-DSC, Netzsch STA 449F3, Germany) in the temperature range of 50 to 1200 °C and a heating rate of 20 °C min -1 , nitrogen flow rate: 50 mL min -1 .

[0057] The thermal properties of Fe(PFO)3@LM-Al@Fe2O3 were analyzed, such as Figure 7 As shown, Figure 7 TG-DSC curve of Fe(PFO)3@LM-Al@Fe2O3.

[0058] like Figure 7 The effect of Fe2O3 as a coating medium on the thermal oxidation performance of Fe(PFO)3@LM-Al was observed using simultaneous thermal analysis technology (TG-DSC). The test atmosphere was nitrogen. It can be seen from the figure that the mass of Fe(PFO)3@LM-Al@Fe2O3 composite particles began to show a downward trend at around 300℃.

[0059] It was observed that an exothermic peak was detected at around 440°C for the composite particles. According to the research of Pantoya et al., this exothermic peak was attributed to the pre-ignition reaction of the aluminum powder: the molecular chain of Fe(PFO)3 broke after thermal decomposition, and the decomposition products thermally moved in the system in the form of gaseous fluorocarbon fragments, causing part of the fluorine element to be locked on the surface of the aluminum particles, that is, the aluminum powder reacted with the coating layer to produce AlF3 through a chemical exothermic reaction.

[0060] Although the TG curve of Fe(PFO)3@LM-Al@Fe2O3 composite particles shows a significant thermal weight loss, the endothermic peak formed by the thermal decomposition of Fe(PFO)3 near 340°C does not appear on the DSC curve of Fe(PFO)3@LM-Al@Fe2O3 composite particles. This may be because the exothermic effect formed by the pre-reaction of aluminum powder and Fe(PFO)3 is greater than the endothermic effect caused by the thermal decomposition of Fe(PFO)3, so an exothermic peak appears at this temperature.

[0061] The DSC curve of pure micron aluminum powder shows an aluminum core melting endothermic peak at around 660℃. However, the DSC curve of Fe(PFO)3@LM-Al@Fe2O3 composite particles shows a large exothermic peak at around 605℃ before the melting point, which is attributed to the following aspects: the surface of pure aluminum powder is treated with liquid metal, resulting in the initial embrittlement of the aluminum shell; the gaseous small molecules produced by the decomposition of fluoride react with the aluminum powder to pre-ignite, destroying the embrittled aluminum shell, and the heat released by this reaction further promotes the rupture of the embrittled aluminum shell; after the above steps, cracks appear in the aluminum shell, and the internal aluminum core makes initial contact with the external oxidation environment through the cracks, and an aluminothermic reaction occurs. The heat released by the aluminothermic reaction back-attacks the aluminum particles, playing a positive cycle role, further promoting the rupture of the aluminum shell, and more aluminum cores are melted and contacted with the external oxygen environment, which is reflected in the thermal oxidation exothermic peak occurring before the melting point of the aluminum powder.

[0062] Therefore, the present invention adopts a fluoride-modified liquid metal medium thermite of the above-mentioned structure and its preparation method, innovatively introduces liquid metal to etch the surface of aluminum powder, and prepares high-purity fluoride Fe(PFO)3, which forms composite particles with LM-Al core-shell, and further coats iron oxide particles on its surface to form a composite energetic compound, and utilizes the pre-ignition exothermic reaction of fluoride and aluminum powder to increase the high-temperature thermal oxidation reaction temperature of aluminum powder to before the melting point of 660°C, thereby achieving a breakthrough in the heat and mass transfer process of aluminum powder.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A fluoride-modified liquid metal medium thermite and a preparation method thereof, characterized in that: The high-activity thermite is prepared by compounding fluoride, iron oxide and aluminum powder, and the preparation method thereof specifically comprises the following steps: Step 1, preparation of liquid metal: using Galinstan eutectic of Ga: In: Sn = 68: 22: 10, with a melting point of -19°C, to prepare liquid metal, the obtained liquid metal is convenient for mechanical stirring at room temperature; Step 2, preparation of aluminum powder / liquid metal composite energetic particles: synthesizing aluminum powder and liquid metal by physical mixing and ultrasonic treatment to obtain liquid metal modified aluminum; Step 3, preparation of iron perfluorooctanoate: adding FeCl3·6H2O to a perfluorooctanoic acid aqueous solution, stirring and mixing, and then performing a hydrothermal reaction. The obtained product is washed to obtain Fe(PFO)3; Step 4, preparation of Fe(PFO)3@LM-Al perfluorooctanoate iron-liquid metal modified aluminum composite particles: mixing liquid metal modified aluminum with perfluorooctanoate iron, and treating by ultrasonication; Step 5, preparation of Fe(PFO)3@LM-Al@Fe2O3 energetic compound: Fe(PFO)3@LM-Al and iron oxide were added into anhydrous ethanol in a mass ratio of 4:3 and ultrasonically stirred and mixed to obtain Fe(PFO)3@LM-Al@Fe2O3.

2. A fluoride-modified liquid metal medium thermite and a preparation method thereof according to claim 1, characterized in that: The specific process of step 2 is as follows: use ultrasonic stirring with a power of 200 W and a frequency of 40 kHz to mix the aluminum powder and the liquid metal for 8 hours, and then perform vacuum filtration to obtain liquid metal-modified aluminum.

3. A fluoride-modified liquid metal medium thermite and a preparation method thereof according to claim 2, characterized in that: When the aluminum powder and the liquid metal are mixed, the proportion of the liquid metal is adjusted to 10%.

4. The fluoride-modified liquid metal medium thermite and the preparation method thereof according to claim 3, characterized in that: The obtained liquid metal modified aluminum was dried in an oven at 50° C. for 12 h.

5. The fluoride-modified liquid metal medium thermite and the preparation method thereof according to claim 1, characterized in that: The specific preparation process in step 3 is as follows: add 10 mL of 0.1 mmol·mL -1 Perfluorooctanoic acid aqueous solution: weigh 4 mmol FeCl3·6H2O and add it to the perfluorooctanoic acid aqueous solution; after fully stirring the mixed solution at 50°C for 1 hour, transfer it to a hydrothermal autoclave and react it in an oven at 100°C for 12 hours to obtain a product after the reaction.

6. The fluoride-modified liquid metal medium thermite and the preparation method thereof according to claim 5, characterized in that: Finally, the obtained product was washed and dried in an oven at 60° C. for 24 h to obtain iron perfluorooctanoate.

7. The fluoride-modified liquid metal medium thermite and the preparation method thereof according to claim 1, characterized in that: The specific preparation process in step 4 is as follows: using ultrasonic stirring with a power of 200 W and a frequency of 40 kHz, the liquid metal-modified aluminum and Fe(PFO)3 are ultrasonically stirred in 20 ml of anhydrous ethanol until the solvent is completely evaporated; the resulting mixture is vacuum filtered and dried in an oven at 50°C for 12 hours to obtain Fe(PFO)3@LM-Al.

8. The fluoride-modified liquid metal medium thermite and the preparation method thereof according to claim 1, characterized in that: In the step 5, the ultrasonic stirring condition is to stir the mixture under ultrasonic stirring with a power of 200 W and a frequency of 40 kHz, and the obtained mixture is dried in an oven at 50° C. for 12 hours to obtain Fe(PFO)3@LM-Al@Fe2O3.

Citation Information

Patent Citations

  • Core-shell structure thermite as well as preparation method and application thereof

    CN113105298A

  • Copper perfluorooctanoate-aluminum powder energetic composite particle and preparation method thereof

    CN115703690A

  • Method for improving metal acceleration capacity of composite explosive

    CN117945819A

  • Aluminum powder / perfluorocarboxylate energetic composite particle and preparation method thereof

    CN118878407A

  • Preparation method of composite thermite and application of composite thermite in 5, 5 '-bistetrazole-1, 1'-dihydroxylammonium diformate

    CN118930391A

Cited By

  • Indium-doped induced aluminum thermal oxidizer and method of making

    CN122586138A